Association of lymphocyte-to-monocyte ratio with in-hospital and long-term major adverse cardiac and cerebrovascular events in patients with ST-elevated myocardial infarction - Wang, Qian (Medicine (Baltimore), 2017)
In recent years, lymphocyte-to-monocyte ratio (LMR) has become a novel indirect marker of inflammation, which has been demonstrated to be associated with poor prognosis of oncology and cardiovascular disease. The aim of the study was to assess the relationship between LMR on admission and in-hospital and long-term major adverse cardiac and cerebrovascular events (MACCE) in patients with ST-elevated myocardial infarction (STEMI) after primary percutaneous coronary intervention (PCI). A total of 306 STEMI patients were enrolled and grouped according to tertiles of LMR from the blood samples obtained in the emergency room on admission. Total white blood cell count, differential count of neutrophil, lymphocyte, monocyte, and other factors were evaluated. The median follow-up period was 21 months (1–36 months). As the LMR decreased, in-hospital nonfatal myocardial infarction and cardiovascular mortality increased (P = .002, P = .009, respectively). And long-term stroke/TIA, TVR, nonfatal myocardial infarction, and cardiovascular mortality also increased with decreasing LMR (P = .012, P = .001, P = .003, P = .002, respectively). The receiver operating characteristic (ROC) curve of LMR for predicting MACCE showed the sensitivity of 76% and specificity of 78% and the optimal cut-off value was determined as 2.62. In multivariate analysis, after adjusting for confounders, LMR was an independent predictor of in-hospital and long-term MACCE (odds ratio [OR] 1.192 [1.069–1.315] P < .001, OR 1.239 [1.125–1.347] P < .001, respectively). The LMR is an independent predictor of in-hospital and long-term MACCE in patients with STEMI after primary PCI. Our results suggest that this simple, inexpensive, relatively available inflammatory marker may have significant effects on the treatment and prognosis in patients with STEMI.